Facilitators and Barriers to Breastfeeding Practices of Mothers in a Selected Urban Community in Malaysia - Muniandy, Naleena Devi; Yusof, Fatin Iman Najihah Mohamad (Jurnal Gizi dan Pangan, 2021)
This study was designed to explore the facilitators and barriers of breastfeeding practices among mothers in a selected urban population in Malaysia. This study reports the qualitative findings from a larger study that was conducted in two health clinics in Selangor, Malaysia. Ten mothers were recruited and an in-depth interview using grounded theory approach was used to obtain information. Interviews were transcribed and was manually arranged into codes and themes using thematic analysis. Facilitators to breastfeeding in this population were maternal factors (knowledge of breastfeeding, intention to breastfeed, perceived benefits of breastfeeding), social support and health care provider. Barriers to breastfeeding were insufficiency of breastmilk, employment and stigma of public breastfeeding. The findings of this study suggest that intervention to improve breastfeeding uptake should aim on increasing knowledge of mothers on coping with issues related to breastfeeding difficulties such as how to increase or sustain milk production and increasing awareness of employers and public on supporting breastfeeding mothers.